'Should we stop or continue conventional synthetic (including glucocorticoids) and targeted DMARDs before surgery in patients with inflammatory rheumatic diseases?'. Issue 2 (27th July 2020) - Goodman, Susan M; George, Michael D
Abstract : Total hip and total knee arthroplasty) remain important interventions to treat symptomatic knee and hip damage in patients with rheumatoid arthritis, with little change in utilisation rates despite the increasingly widespread use of potent conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) and targeted DMARDs including Janus kinase inhibitors and biologics. The majority of patients are receiving these immunosuppressing medications and glucocorticoids at the time they present for arthroplasty. There is minimal randomised controlled trial data addressing the use of DMARDs in the perioperative period, yet patients and their physicians face these decisions daily. This paper reviews what is known regarding perioperative management of targeted and csDMARDs and glucocorticoids.